”Wielka Brytania, wielkie nadzieje”: reprezentacja polskiej migracji w Londyńczykach - Rydzewska, Joanna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2012)
‘Great Britain, Great Expectations’: The Representation of Polish Migration to Great Britain in Londyńczycy/Londoners Following the 2004 expansion of the European Union (EU), Polish migrant workers began arriving in the United Kingdom on an unprecedented scale. Londoners (Londyńczycy, 2008-9) was a response to this. Exploring the lives of Polish migrants in London, the series became an instant success on Polish television, regularly attracting around four million viewers. This article explores how Londoners represents Britishness and Polishness to its target Polish audience. It will argue that the series negotiates questions of Polish national identity, which over the past 20 years has been undergoing fundamental redefinition as a result of the ending of the Cold War and Poland’s accession to the EU.